The basic public finance of public-private partnerships - Eduardo M. R. A. Engel; Ronald D. Fischer; Alexander Galetovic (Yale University, Economic Growth Center, 2007)
Public-private partnerships (PPPs) cannot be justified because they free public funds. When PPPs are justified on efficiency grounds, the contract that optimally balances demand risk, user-fee distortions and the opportunity cost of public funds, features a minimum revenue guarantee and a revenue cap. However, observed revenue guarantees and revenue sharing arrangements differ from those suggested by the optimal contract. Also, this contract can be implemented via a competitive auction with realistic informational requirements. Finally, the allocation of risk under the optimal contract suggests that PPPs are closer to public provision than to privatization.
Keywords: H21; H54; L51; R42; 330; Bundling; cost of public funds; demsetz auction; minimum revenue guarantees; privatization; revenue and profit caps; scope of government; subsidies.